2009
DOI: 10.1002/pits.20386
|View full text |Cite
|
Sign up to set email alerts
|

Grade retention: Current decision‐making practices and involvement of school psychologists working in public schools

Abstract: Research examining student outcomes (e.g., achievement, adjustment) after grade retention reveals that it does not result in long-term improvements for students; however, grade retention continues to be used as an intervention. The purpose of this study was to examine retention decision-making practices, as well as school psychologists' knowledge, beliefs, and opinions regarding retention. Actual and ideal roles of school psychologists in grade retention decisions were also examined. Participants included 250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…Retention often carries a perception of student failure, lack of support from teachers and the school, and negative socioemotional effects for the student, such as increased frustration and disengagement. Retention continues to be a common form of intervention for students who have been deemed unprepared for the next level of cognitive and social development, despite the known deleterious impacts on student dropout rate, attitudes towards school, and engagement (Schnurr, Kundert, & Nickerson, 2009). Schnurr et al (2009) cite multiple examples of research on retention and academic outcomes, with findings indicating small short-lived improvements in achievement (Jimerson, 2001;Gleason, Kwok, & Hughes, 2007) but no long-term improvement for retained students (Holmes & Matthews, 1984;Holmes, 1989;Jimerson, 2001).…”
Section: Grade Repetition (Retention)mentioning
confidence: 99%
See 1 more Smart Citation
“…Retention often carries a perception of student failure, lack of support from teachers and the school, and negative socioemotional effects for the student, such as increased frustration and disengagement. Retention continues to be a common form of intervention for students who have been deemed unprepared for the next level of cognitive and social development, despite the known deleterious impacts on student dropout rate, attitudes towards school, and engagement (Schnurr, Kundert, & Nickerson, 2009). Schnurr et al (2009) cite multiple examples of research on retention and academic outcomes, with findings indicating small short-lived improvements in achievement (Jimerson, 2001;Gleason, Kwok, & Hughes, 2007) but no long-term improvement for retained students (Holmes & Matthews, 1984;Holmes, 1989;Jimerson, 2001).…”
Section: Grade Repetition (Retention)mentioning
confidence: 99%
“…Retention continues to be a common form of intervention for students who have been deemed unprepared for the next level of cognitive and social development, despite the known deleterious impacts on student dropout rate, attitudes towards school, and engagement (Schnurr, Kundert, & Nickerson, 2009). Schnurr et al (2009) cite multiple examples of research on retention and academic outcomes, with findings indicating small short-lived improvements in achievement (Jimerson, 2001;Gleason, Kwok, & Hughes, 2007) but no long-term improvement for retained students (Holmes & Matthews, 1984;Holmes, 1989;Jimerson, 2001). Further, the long-term impacts of retention on student performance have been shown to be nonsignificant (Jimerson, 1999;Silberglitt, Jimerson, Burns, & Appleton, 2006;Jimerson & Ferguson, 2007).…”
Section: Grade Repetition (Retention)mentioning
confidence: 99%
“…In this case, the staff meeting considers the likelihood that a family rejects an LPA-proposition, the probability that the student improves enough during the repeated grade so that she can be admitted to LGT and 'costs' of retaining the student. These 'costs' consist of an increased economic burden for the school and for higher administrative institutions because retention increases class sizes, the need for teachers and for learning material (Schnurr, Kundert and Nickerson, 2009). School staff also wants to avoid high rates of grade repetitions because these indicate that a school system is poorly performing (Ryan and Watson, 2006) and because the French government requires them to be kept low (Masson, 1994(Masson, , 1997.…”
Section: Staff Meeting's Decision-makingmentioning
confidence: 99%
“…A study analyzing results of teacher surveys found that 44% of teachers indicated that their source of knowledge regarding retention came from personal experiences, with 22% reporting they gained their knowledge by discussing the practice with colleagues, and only 9% obtaining their knowledge from grade repetition literature or participation in workshops (Witmer et al, 2004). This was consistent with personal experience; teachers related to the positive effects grade repetition has on students during the repeat year, but fail to observe and do not accept, that the benefits diminish over time and new problems emerge in the repeaters' future (Schnurr et al, 2009). These teachers saw temporary advantages to grade repetition, but did not see that these advantages fade away over time (Bropy, 2006).…”
Section: Grade Repetition Determinantsmentioning
confidence: 54%
“…Bonvin et al (2008) completed nationwide, empirical, three measurement points, longitudinal research regarding student retention and found that determinants for the practice were largely underdeveloped. Schnurr, Kundert, and Nickerson (2009) agreed there was limited information regarding the uniformity of how a retention decision was made and, more specifically, for which type of child. This functioned as a primary barrier to effective action for the student who was under performing.…”
Section: Grade Repetition Determinantsmentioning
confidence: 99%